Integrating Radiation Oncology Into Undergraduate Medical Education - Mona Arbab, MD; Jordan A. Holmes, MD, MPH; Kenneth R. Olivier, MD; Emma C. Fields, MD; Kimberly S. Corbin, MD; Jenna M. Kahn, MD; Richard C. Zellars, MD; Antwione M. Haywood, PhD (Advances in Radiation Oncology, 2021)
Cancer is one of the most important public health problems. However, medical education has not advanced at the same rate when it comes to cancer education. Currently, the United States Medical Licensing Examination subject examinations do not cover radiation oncology, prevention, and survivorship planning in its assessment model. Incorporating medical oncology and radiation oncology training into the undergraduate medical education curriculum can have a significant benefit in training future physicians. In this paper, we review current literature and propose some ideas that can help incorporate oncology, and specifically radiation oncology, into undergraduate medical education.